2016
DOI: 10.1177/0363546516632332
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Noncontact Anterior Cruciate Ligament Injuries Is Not Associated With Slope and Concavity of the Tibial Plateau in Recreational Alpine Skiers

Abstract: Despite differences between sexes in knee anatomy and the injury risk, the sagittal and coronal slopes (LTS, MTS, CTS), as well as the concavity of the medial tibial plateau (MTD), were not associated with the risk of an ACL tear during a noncontact injury among recreational alpine skiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
21
1
1
Order By: Relevance
“…On the contrary, some authors propose that neither anatomical variation poses a risk. [17][18][19][20][21] Three relevant meta-analysis studies on this subject have also reported conflicting conclusions. Zeng et al concluded that both medial and LTS were risk factors for both genders.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, some authors propose that neither anatomical variation poses a risk. [17][18][19][20][21] Three relevant meta-analysis studies on this subject have also reported conflicting conclusions. Zeng et al concluded that both medial and LTS were risk factors for both genders.…”
Section: Discussionmentioning
confidence: 99%
“…There has been extensive discussion regarding the relationship between ACL injury and the tibial slope which remained controversial. [131421] Alentorn-Geli et al [13] suggested that an increased posterior tibial slope may be associated with ACL injury in male patients, but the association between ACL injury and the angle formed by the Blumensaat line and the anterior tibial slope in male patients requires more investigation. Dare et al [14] found that the lateral tibial slope was significantly associated with an increased risk of ACL injuries in pediatric and adolescent patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the early years of ACL research, many clinical studies and high-quality meta-analyses were conducted to identify the association between the tibial slope and ACL injury, but the results were inconsistent. [131419202122] Several studies found differences in the anatomic risk factors between men and women. [1123] In addition, one study suggested that the medial tibial plateau slope and lateral tibial plateau slope should be measured separately due to their opposite effects on ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the spontaneous rupture of a dog CCL often occurs during normal activities, such as walking or running. By contrast, human ACL rupture occurs most commonly during sporting activity 88 . Although the underlying mechanisms of CCL pathology are undefined, predisposed dogs have thinner collagen fibrils in weaker CCLs that have increased expression of matrix metalloproteinase 2 than those of cruciate disease-resistant breeds such as Greyhounds 82 .…”
Section: Knee Cruciate Ligament Rupturementioning
confidence: 99%